Kaji Eksperimental Turbin Air Tipe Undershot Untuk Pembangkit Listrik Tenaga Air Dipasang Secara Seri Pada Saluran Irigasi - Riko Fernando; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The irrigation canal available throughout the Tarmland in Province of Riau. The irrigation system can be utilized as hydropower generation even if the possibility can only move a small-scale water turbine, but when made in large quantities would produce large amounts of energy. In this study tested the water turbine type undershot with installation of turbines in series on the flow of irrigation and compare them with the installation of turbine singly. From the testing that has been done the efficiency of turbines produced at the time of testing in series lower than in a single test, this is because at the time of testing the water flowing series obstructed by the second turbine, thus making the water flow is not smooth. The highest power generated main turbine installed in series is 153.66 Watt on water flow of 0.308 m3/ s, the highest power generated while the main turbine installed singly is 196.25 Watt on water flow of 0.308 m3/s.Keywords: Irrigation canal, Undershot Water Turbine, series Tested.